Primavera: A new therapeutical approach to vulvo-vaginal atrophy - Amori, Paolo; Di Nardo, Veronica; Vitiello, Gabriella; Franca, Katlein; Hercogova, Jana; Wollina, Uwe; Daaboul, Farah; Tchernev, Georgi; Lotti, Torello (Dermatologic therapy, 2018)
Vulvovaginal atrophy is a condition that affects women, although it is mainly associated with the onset of menopause mainly due to hormonal changes vulvovaginal laxity and mucosal atrophy can also affect women at different life stages such as after pregnancy or for cancer patients who have undergone chemo or endocrine therapy. This condition negatively influence quality of life, sexual desire, and self-confidence. Many therapies have been considered mainly with inconclusive or transient results in terms of benefit factor. Recently, a new non-invasive product, containing hyaluronic acid, oligopeptides, and antioxidants was introduced to the market. Its name is "Primavera," by Renaissance, Italy. The aim of this product is to allow a vulvo-vaginal biostimulation and considered simple, safe, and satisfactory.
Keywords: Oligopeptides; vaginální onemocnění; Antioxidants; Female; výsledek terapie; ženské pohlaví; Vagina; lidé; oligopeptidy; Recovery of Function; Treatment Outcome; primavera; Vulva; Vaginal Diseases; atrofie; obnova funkce; Rejuvenation; Vulvar Diseases; omlazení; Atrophy; antioxidancia; vulvovaginal atrophy; nemoci vulvy; hyaluronic acid; vulva; vagina; Humans